Affine nonmagnetic transformation design and its application - Xu, Hongyi (2013)
Based on the transformation optical design which possesses simultaneously unitary permeability and piece-wise homogeneity, transformation-optics devices can practically avoid magnetism and inhomogeneous parameters, and be implemented directly using existing dielectric materials with ideal performance.